Steel beam under combined action of bending and torsion-a non destructive approach - Bhatnagar, S.D.; Sehgal, V.K.; Gopal, Krishna (Journal of Structural Engineering, 2024)
Rolled steel joists (RSJ) are used as beam in bridges and multistory buildings. Structural integrity of these beams is to be monitored to safeguard human lives. Regular periodic non-destructive investigation right from fabrication enables the user to achieve optimum safe utilization under design load. It also alarms untoward deterioration caused due to different parameters. This paper presents results of analytical study on behavior of steel beam subjected to combined action of bending and torsion. A non-destructive testing setup has been proposed to study the elastic/plastic torsional deformation represented by expressions including torsional moments, shear modulus and polar moment of inertia. Spectrum analysis has been chosen as the technique of signal analysis to study the relationship. Limit state approach has been adopted for analysis under different load combinations, end conditions and sectional properties.